Studi Analisis Penggantian Agregat Halus Dengan Padas Giling Terhadap Kuat Tekan Mortar - M. Miftahul Rohman N. A.; Wysmo Suryo W; Martono Martono; Sutarno Sutarno (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2018)
In the district of Pati, precisely in the area of Gedudero Village, Sukolilo District, is one of the milled corners. Milled Padas can be applied as a substitute for sand and stone times on the foundation. The purpose of this study was to find out the physical  haracteristics (compressive strength) mortar mixture of ground beans and utilize milled pad as a substitute of fine aggregate in the manufacture of efficient mortar.The specimens made are cube shaped pieces of 5 cm x 5 cm x 5 cm with mixture ratio 1 PC: 4 Sand; 1 PC: 3 Sand: 1 Grind Padas; 1 PC: 2 Sand: 2 Grind Padas; 1 PC: 1 Sand: 3 Grind Padas; 1 PC: 4 Grind Padas. From the graph of test results of 28-day mortar strength pressures, it is known that the maximum compressive strength achieved by mortar with a mixture ratio of 1 PC: 3 Sand: 1 Grind Padas mixture of 144.84 kg / cm2. Mortar is made without using a mixture of grind padas with a ratio of 1 PC : 4 Sand yields a compressive strength of 132.88 kg / cm2. For the lowest compressive strength, obtain on mortar with mixture cement 1 Cement: 4 Grind padas of 109.80 kg / cm2. While to obtain an efficient mixture, obtained on mortar with a mixture of 1 PC: 1 PS: 3 PG. This grind padas can replace the sand with a certain mixture ratio.Kata kunci : grind padas, compressive strength, mortar